Potensi Daun Surian (Toona sureni) sebagai Bahan Tambahan Pangan dalam Pengembangan Kerupuk - Mutmainnah; Anni Faridah; Yuliana; Sari mustika (LPPM Universitas Negeri Jakarta, 2025)
Crackers are a popular snack enjoyed by various groups due to their crispy texture and savory flavor. However, crackers are low in nutritional value. Surian leaves (Toona sureni) are a regional plant rich in bioactive compounds, including flavonoids, polyphenols, alkaloids, and terpenoids, which provide health benefits. This study aimed to evaluate the impact of adding surian leaves at concentrations of 0%, 7%, 13%, and 18% on the quality of crackers, particularly in terms of color, aroma, texture, and taste. The research employed an experimental approach using a completely randomized design (CRD) consisting of four treatments and three replications. The study was conducted from September 2024 to May 2025 at the Culinary Workshop, Department of Family Welfare Sciences, Faculty of Tourism and Hospitality, Universitas Negeri Padang, involving 30 panelists. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) when the calculated F-value exceeded the critical F-value. Findings revealed that the addition of surian leaves significantly affected the color and aroma quality of the crackers, which were further evaluated using the Duncan test. However, the addition did not affect the texture and taste quality.. The optimal treatment was identified at 13% surian leaf addition (X₂), yielding sensory scores of 4.83 (X₂) for cream-colored appearance with green spots, 5.90 (X₂) for distinctive surian leaf aroma, 5.76 (X₂) for crispy texture, and 6.08 (X₂) for savory taste. The hedonic test results showed the highest scores for color at 5.32 (X₂) (liked), texture at 5.45 (X₂) (liked), aroma at 5.20 (X₂) (liked), and taste at 5.78 (X₂) (strongly liked). Crackers with 13% surian leaves demonstrated the optimal treatment, producing the highest quality and level of preference.